Coronenohelicenes with Dynamic Chirality - Weiß, Corinna; Sharapa, Dmitry I.; Hirsch, Andreas (Chemistry - A European Journal, 2020)
The synthesis of a new type of chiral and dynamic nonplanar aromatics containing a combination of fused perylene-based coronenes and helicenes is reported. Either one or two helicene moieties were fused to the bay regions of an extended perylene core. The target compounds contain either identical or two different helicene building blocks. The combination with two helicene units leads to six different isomers, including two pairs of enantiomers and two meso forms. The experimental determination of the isomerization barriers the corresponding double [5]-helicenes revealed activation energies of Ea=24.81 and 25.38 kcal mol−1, which is slightly above the barrier of the parent [5]-helicene. Resolution of all possible regio- and stereoisomers allowed for the systematic investigation of the chiroptical properties. They revealed remarkable dissymmetry factors IgabsI of up to 1.2×10−2, which mirror the synergy between the strong absorbing perylenes and the inherent chirality of helicenes.
CRIS-Team Scopus Importer:2020-10-02
Keywords: dynamic; helicene; isomerization; isomers; perylene